Teaching Our Violent History: Shifting Opinions on Peace and War through Information and Media Frames - Lees, Sam (2020)
I expand the current research on how graphic images in accounts of historical violence impact students’ views on war, peace, violence, and the role of the international community. By first manipulating the amount of violent detail and images in an article on the Rape of Nanking, I measure the shifts in opinions on 1) the inevitability of war, 2) the violence of human nature, 3) the level of conflict in the world today, and 4) the role of the international community in punishing war crimes. I also measure shifts in 5) the level of importance placed on teaching historical violence and ask 6) if students shown graphic images support their use in education settings. Surprisingly, I find that students shown violent images were less likely to report that humans are inherently violent. Students were also less likely to support using violent images in educational settings